Safety of early Hartmann reversal during adjuvant chemotherapy in colorectal cancer: a pilot study - Kim, Dong Ha; Lee, Kyung-Ha (Frontiers in Surgery, 2023)
Introduction: Most patients undergoing the Hartmann procedure for complicated colorectal cancer require chemotherapy because of their advanced status. Stoma created during the procedure is typically closed after the completion of postoperative chemotherapy. However, stomas can induce medical or surgical complications and disturb quality of life. This study aimed to evaluate the safety of Hartmann's reversal during postoperative chemotherapy.Methods: We conducted a retrospective review of electronic medical records. Between 2017 and 2021, 96 patients underwent Hartmann reversal for after colorectal cancer surgery. Among them, the number of patients who underwent Hartmann procedure with radical resection of complicated colorectal cancer and Hartmann reversal during adjuvant chemotherapy was 13. The clinical, surgical, and pathological characteristics of the patients were evaluated.Results: Eight and five patients had obstructions and perforations, respectively. Two patients with synchronous liver metastases underwent simultaneous liver resection and reversal simultaneously. Five and eight patients received adjuvant chemotherapy with capecitabine and FOLFOX, respectively. The median interval between the Hartmann procedure and reversal was 3.31 months (2.69-5.59). The median operative time for Hartmann's reversal was 190 minutes (100-335). The median hospital stay was 10 days (7-21). Four patients (30.8%) developed postoperative complications, and the rate of 3 or higher grade according to the Clavien-Dindo classification within 90 days postoperatively was 0%. Except for 1 patient who refused continuation of chemotherapy, 12 patients completed the planned chemotherapy. Median total duration of adjuvant chemotherapy was 6.78 months (5.98-8.48). There was no mortality. Conclusion: Early Hartmann reversal during adjuvant chemotherapy is tolerable and safe in carefully selected patients. In particular, it can be used as a therapeutic option for patients with complicated colorectal cancer with synchronous resectable metastases.